Benefits of Vestibular Exercises Affecting Performance in Early Childhood - Claassens, Heidi (Absorbent Mind, 2025)
Specifically will explore the effects of vestibular exercises on sensory and motor systems, as well as emotional and social regulation, which impact the performance of early childhood learners. This qualitative study is grounded in the constructivist paradigm, involving the participation of eight Grade 1 learners, eight Grade 2 learners, and eight Grade 3 learners in South Africa. Additionally, three parents completed weekly observation sheets to monitor the learners' performance. Data collection techniques in this study used questionnaires and observations. The result shows that vestibular exercises serve as a relay, transferring signals to other sensory systems, which then convey them to the motor system. This interconnected process is likely to impact scholastic performance positively. By framing this within the social model theory, we recognize the importance of creating an inclusive environment where all learners can engage in these exercises. This model emphasizes the role of societal structures in enabling or restricting participation, highlighting that providing access to vestibular exercises can reduce barriers and promote equal developmental opportunities. Hence, it can be concluded that vestibular exercises benefit developmental areas in early childhood, thereby influencing academic performance. Through the social model theory lens, this underscores the importance of inclusive practices that support all learners in reaching their full potential.